Distributed meter data aggregation framework based on Blockchain and homomorphic encryption. Issue 1 (9th January 2019) - Wang, Yuxuan; Luo, Fengji; Dong, Zhaoyang; Tong, Ziyuan; Qiao, Yichen
Abstract : A significant progress in modern power grids is witnessed by the tendency of becoming complex cyber‐physical systems. As a fundamental physical infrastructure, smart meter in the demand side provides real‐time energy consumption information to the utility. However, ensuring information security and privacy in the meter data aggregation process is a non‐trivial task. This study proposes a distributed, privacy‐preserving, and secure meter data aggregation framework, backed up by Blockchain and homomorphic encryption (HE) technologies. Meter data are aggregated and verified by a hierarchical Blockchain system, in which the consensus mechanism is supported by the practical Byzantine fault tolerance algorithm. On the top of the Blockchain system, HE technology is used to protect the privacy of individual meter data items during the aggregation process. Performance analysis is conducted to validate the proposed method.